Genic and genetic drift effects associated with intrapopulation recurrent selection in the SA3 maize population - Capeda, Mario Caviedes; Junior, Cláudio Lopes de Souza; Pandey, Shivaji; Leon, Luis Narro (Pesquisa Agropecuaria Brasileira, 2000)
The effects of intrapopulation recurrent selection and of the genetic drift were evaluated on 20 cycles of selection for SA3 maize (Zea mays L.) population, tolerant to acid soil conditions. A sample of eight cycles was used to estimate the response to selection for grain yield and other agronomic traits by the model proposed by Smith (1983). The genetic materials used included eight cycles per se, eight cycles per se selfed, 28 F1's among cycles, 28 F1's among cycles selfed and 28 F1's recombined. The trials were evaluated at five environments under acid soils conditions in Brazil and Colombia. The estimates of response to selection (2ALI+2DLI) showed that selection process was not effective to improve grain yield and to reduce plant height. However, the selection procedure was efficient to reduce days to silk and to increase the number of ears per plant. The magnitude of genetic drift estimates (DQI) indicated that its effects did not limit the improvement of the characters evaluated.
Keywords: Zea mays; acid soils; agronomic characters; grains; production; genetic variation; selection responses